Preparation and determination of total anthocyanins extraction from the skin of vigna cylindrica skeels (Dolichos catjang Burm. f) - Pham, Tri Nhut; Vo, Dai-Viet N.; Lam, Tri Duc; Vy, Tran Anh; Toan, Tran Quoc; Vu-Quang, Hieu; Nhan, Le Thi Hong; Nguyen Quynh Anh, Phan; Bui, Le Minh (IOP Publishing, 2019)
Because of antioxidative potential, anthocyanins become more and more popular in various fields including food products and pharmaceutical industries. The extraction technique has a great effect on the quality of natural color. Seed coat color is an essential part of customer choices for cowpea (Vigna unguiculata L. Walp). The experimental study was conducted to determine the effect of different extracting parameters such as duration of extraction, different extraction of temperature (20 - 90oC), duration of extraction (30 - 90 min) and solid-liquid ratios (2:1 - 10:1 mL/g) and solvent concentration (H2O : Ethanol) were selected in order to extract anthocyanin from Vigna cylindrica Skeels. The highest anthocyanin content of 205.58 mg/L was collected at 50% enathol, the solid/liquid ratio 6:1 (mL/g), extraction time 60 (min), and temperature 60 (oC). The results showed that different extraction media can significantly affected the anthocyanins content of the valuable source Vigna cylindrica Skeels extracts.